Microsoft Access: everything you need to know to manage to manage your database effectively (Research, Society and Development, 2023)
This article provides a comprehensive and detailed overview of Microsoft Access, a versatile database manager used in both business and personal contexts. Through bibliographic research, including articles and specialized books, as well as personal experiences, we seek to present a complete analysis of the software. The text covers from fundamental concepts to advanced features of Access, exploring different perspectives of use and ensuring the security of the stored data. By discussing essential aspects and effective management techniques, the article aims to optimize the user experience with the program. Throughout the study, information is projected on the basic functionalities of the software, such as creating and manipulating tables, forms, reports and queries, as well as advanced features such as VBA programming and integration with other Microsoft applications. In addition, the article explores varied perspectives of use, highlighting the potential of Access in a variety of scenarios and meeting different data management needs. Finally, emphasis is placed on data security in Access, addressing practices and settings that ensure the protection of stored information. With a complete and didactic approach, the article aims to make the use of Microsoft Access as efficient as possible for users.